Pengaruh Penempatan dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Pengolahan CPO - Moh Roni; Y Rahmat Akbar; Loveana Syaifora (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2021)
The research was conducted on processing section Crude Palm Oil PT Eluan Mahkota that aimed to figure out the impact of placement, work environmet of work productivity, either simultaneously or partially. The population of the research was all of the processing section Crude Palm Oil PT Eluan Mahkota. Total sample of 83 respondents on processing section Crude Palm Oil PT Eluan Mahkota. The sampling technique used is simple random side and multiple linier regression analysis. Simultaneous regression (F test) showed that the independent variables studied (Placement and Work Environment) together (simultaneously) have a significant influence on the dependent variable (Work Productivity). Partial test (t test) shows, the independent variables have a significant effect on effectiveness of Work Productivity. There is a high contribution of the variable placement and work environment on the Effectiveness of work productivity in processing section Crude Palm Oil PT Eluan Mahkota, the illustrated by the coefficient of determination obtained. From the result of this research which should be observed is the effectiveness and efficiency of employees to be able to achieve maximum result. Placement must be conform with ability of employees. In any situations, employees must be controlling emotions and then works with the existing rules.